Nutritional risk according to Mini Nutritional Assessment– whort form among community dwelling elderly in Kuantan, Pahang: a pilot study - Muhamad, Abdul Rahman; Hamirudin, Aliza Haslinda; Zainudin, Norain; Sidek, Suriati; A. Rahman, Nor Azlina (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Introduction: The risk of developing malnutrition increases with advancing age. It has the potential to place significant burdens on healthcare and other support services. However, studies with regards to malnutrition among community-dwelling elderly population in Malaysia is scarce specifically in Kuantan. The objective of this study was to determine malnutrition risk using the Mini Nutritional Assessment- Short Form (MNA-SF) among community-dwelling elderly people in Kuantan and to investigate its associated factors. Methods: A pilot study was conducted among 73 community-dwelling elderly in Kuantan, Pahang, Malaysia aged 60 years and above. Malnutrition risk of the elderly was evaluated by using Mini Nutritional Assessment– Short Form (MNA-SF). A standardized questionnaire was used to record the factors associated with malnutrition: demographic characteristics, income level, percentage of food expenditure per month, body mass index, physical activity level and disease status. Chi Square test was performed for statistical analysis. Results: The subjects comprised of 39 (53.4%) males and 34 (46.6%) females. Mean age of the subjects was 65.4 ± 5.4 years old. Among 73 subjects, 36.0% were well nourished and 64.0% were at malnutrition risk. Low income (p= 0.045) and physically inactive among elderly subjects (p= 0.039) appeared to be significantly associated with malnutrition risk. Other results were not statistically significant. Conclusions: The findings provide preliminary evidence that malnutrition risk was high among elderly living in Kuantan. Therefore, nutrition screening in a full-scale study is recommended for elderly in order to further identify those at risk of malnutrition in a timely manner. Hence, intervention can be implemented to improve the health status of this population.